ANALISIS USER INTERFACE (UI) DAN USER EXPERIENCE (UX) PADA WEBSITE COFFEE SUFI MENGGUNAKAN METODE HEURISTIC EVALUATION - Galih, Galih; Muhammad, Aang; Imadudin, Imadudin (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Coffee Sufi is a business that focuses on selling coffee, which already has a website as a medium for transactions and promotions, therefore a website must be able to attract the attention of potential customers. To support website design, it is necessary to have periodic developments. Based on research by distributing questionnaires answered by 60 respondents who were taken randomly, namely: the need for improvements to the ordering page through the website by adding several functions such as choosing payment methods, adding order cancellations, ordering history, besides that some argue that in terms of website appearance it requires updating the user interface both in terms of page content composition, icons on the website, in order to produce a good user experience. There are many ways or methods that can be used to evaluate the usability of the user interface and user experience of the website. One of them is the Heuristic Evaluation method. Heuristic Evaluation method is a method that examines the ease of use (usability) and helps find or identify problems that exist in the interface or user interface of a software (Nielsen, 1994).